Contact problems for bodies with complex coatings. (10th December 2019) - Kazakov, Kirill; Kurdina, Svetlana
Abstract : The paper deals with various statements and mathematical models of contact and contact‐wear problems for bodies with coatings. It is shown that the mathematical models for a number of such problems can be represented as a mixed integral equation or a system of mixed integral equations with additional conditions. It is also shown that these equations contain rapidly varying or even discontinuous functions in the case of interaction between bodies of complex shape and with some surface properties. Therefore, it is necessary to use a special approach for constructing efficient analytic solutions. Its implementation is demonstrated by an example.